The Biafran humanitarian crisis, 1967-1970 international human rights and joint church aid - Omaka, Arua Oko (Madison Teaneck Fairleigh Dickinson University Press, 2016)
Introduction -- The colonial design and military incursion -- The Gowon regime and the secession of Eastern Nigeria -- Humanitarian impulse -- Joint church aid: formation and relief organization -- The relief war: obstacles and debates -- Conclusion
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Food relief -- Nigeria, Eastern -- History; Humanitarian assistance -- Nigeria, Eastern -- History; Nigeria -- History -- Civil War, 1967-1970; Nigeria -- History -- Civil War, 1967-1970 -- Civilian relief; Nigeria, Eastern -- History -- 20th century; Hochschulschrift